2017
DOI: 10.1002/ijch.201700104
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli‐responsive Supra‐biomolecular Nanoassemblies of Cucurbit[7]uril with Bovine Serum Albumin: Drug Delivery and Sensor Applications

Abstract: Construction and characterization of stimuli‐responsive supra‐biomolecular nanoassembly between cucurbit[7]uril (CB7) and bovine serum albumin (BSA), uptake and release of doxorubicin (DOX) in live cells, the enhanced sensitivity of brilliant green (BG) and the metal ion‐induced relocation of neutral red (NR) dye to BSA have been discussed in this review. The fluorescence intensity of DOX is largely quenched in the presence of nanoassembly which recovers with adamantylamine or by changing the pH of the solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(156 reference statements)
0
4
0
Order By: Relevance
“…The surface modification of proteins through noncovalent interaction using small receptor molecules such as calixarenes and cucurbiturils has attracted an immense amount of research attention for developing stimuli-responsive biomaterials and biosensors and inhibiting protein aggregation by preventing the conversion of the α-helical structure to the β-sheet structure of the protein. ,, In a previous study, Bhasikuttan et al have demonstrated the synergistic binding of a triphenylmethane dye, i.e., brilliant green (BG) with CB7 and bovine serum albumin (BSA), which enhances the emission intensity of the weakly fluorescent BG by more than 300-fold . Here, CB7 acts as a supramolecular enhancer which cooperatively increases the fluorescence intensity of BSA-complexed BG .…”
Section: Assemblies With Surfactants Proteins and Antibioticsmentioning
confidence: 99%
See 3 more Smart Citations
“…The surface modification of proteins through noncovalent interaction using small receptor molecules such as calixarenes and cucurbiturils has attracted an immense amount of research attention for developing stimuli-responsive biomaterials and biosensors and inhibiting protein aggregation by preventing the conversion of the α-helical structure to the β-sheet structure of the protein. ,, In a previous study, Bhasikuttan et al have demonstrated the synergistic binding of a triphenylmethane dye, i.e., brilliant green (BG) with CB7 and bovine serum albumin (BSA), which enhances the emission intensity of the weakly fluorescent BG by more than 300-fold . Here, CB7 acts as a supramolecular enhancer which cooperatively increases the fluorescence intensity of BSA-complexed BG .…”
Section: Assemblies With Surfactants Proteins and Antibioticsmentioning
confidence: 99%
“…The generated assembly presented the effective uptake and controlled discharge of doxorubicin (DOX), a typical anticancer drug, which has also been endorsed with measurements in live cells . The cell viability experiments established that the DOX-loaded complex mitigates the cytotoxicity of DOX, and the same can be recovered on demand through an external stimulus, activating its therapeutic aspects and being very effective in cancer cells. , Furthermore, such macrocycle-supported protein assemblies would be more promising as a practical methodology to inhibit protein misfolding/aggregation, which is responsible for many neurodegenerative diseases …”
Section: Assemblies With Surfactants Proteins and Antibioticsmentioning
confidence: 99%
See 2 more Smart Citations